2019
DOI: 10.3390/nu12010039
|View full text |Cite
|
Sign up to set email alerts
|

Association of the Dietary Approaches to Stop Hypertension, Physical Activity, and Their Combination with Semen Quality: A Cross-Sectional Study

Abstract: The influence of individual lifestyle factors is widely described in studies on semen quality. However, their synergistic effect is often neglected. The aim of the study was to examine the association between semen quality and dietary approaches to stop hypertension (DASH) diet, physical activity (PA), and the two separately and in combination. A cross-sectional study was carried out among 207 men aged 20-55. Dietary data were collected by a food frequency questionnaire (FFQ) and analysed according to the DASH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(40 citation statements)
references
References 52 publications
(71 reference statements)
1
38
0
Order By: Relevance
“…The authors concluded that medical comorbidities are associated with impaired sperm production and suggested that male infertility evaluation offers not only specific therapy to improve semen parameters but also treatment for non-specific medical comorbidities, which may benefit general health status and spermatogenesis restoration. Several other population-based studies have shown the association between male infertility and hypertension (125)(126)(127). Animal studies have also thrived in this aspect of reproductive research and have provided evidence that hypertension is associated to male infertility (128)(129)(130).…”
Section: Hypertension-induced Os In Male Infertilitymentioning
confidence: 99%
“…The authors concluded that medical comorbidities are associated with impaired sperm production and suggested that male infertility evaluation offers not only specific therapy to improve semen parameters but also treatment for non-specific medical comorbidities, which may benefit general health status and spermatogenesis restoration. Several other population-based studies have shown the association between male infertility and hypertension (125)(126)(127). Animal studies have also thrived in this aspect of reproductive research and have provided evidence that hypertension is associated to male infertility (128)(129)(130).…”
Section: Hypertension-induced Os In Male Infertilitymentioning
confidence: 99%
“…DBI-16 [ 26 ], CHEI [ 27 ], MDS [ 17 ] and DASH score [ 19 , 33 ] were calculated with the dietary intake information collected from FFQ. The DBI-16 has eight food components including cereals, vegetables and fruits, beans and dairy products, animal foods, empty energy foods, condiments, diet variety, and water.…”
Section: Methodsmentioning
confidence: 99%
“…For each food group [ 37 ], a maximum score of 10 could be achieved when the intakes meet recommendation. If lower intakes are favored by DASH diet, reverse scoring is applied [ 19 , 33 ] ( Supplementary Table S4 ). Adherence to the DASH diet is based on the overall score, ranging from 0 to 80.…”
Section: Methodsmentioning
confidence: 99%
“…The AHEI diet adherence, based of food and nutrients predictive of chronic disease risk, showed the best results in total sperm count, concentration, and morphology out of the four dietary patterns [ 269 ]. The impact that male dietary patterns have on male fertility continues to be studied [ 270 , 271 , 272 , 273 , 274 ]; additional studies in a healthy male population could provide a significant point of comparison with infertile men.…”
Section: Future Directions: Foods and Dietary Patterns In Male Infmentioning
confidence: 99%